2013
DOI: 10.1186/1746-6148-9-191
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of remote monitoring of parturition in dairy cattle as a new tool for calving management

Abstract: BackgroundProper calving management of dairy herds is a crucial aspect of the bovine life cycle, as it has profound effects on calf viability and on the post-partum course of the dam. The objectives of this study were to monitor the calving process through the use of a remote alarm system and to determine the impact of prompt emergency obstetric procedures in case of dystocia for the prevention of stillbirths and post-partum reproductive pathologies, and for improving herd fertility. Six groups of experimental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
58
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(59 citation statements)
references
References 31 publications
1
58
0
Order By: Relevance
“…This specific sensor is an intravaginal device from which one module is expelled during the second stage of parturition. This expelled module transmits a signal when it is outside the body (Palombi, et al, 2013). When this sensor system was applied on dairy farms studies reported a significant decrease on calf mortality, uterine infections and number of days open (Palombi, et al, 2013, Paolucci, et al, 2010.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…This specific sensor is an intravaginal device from which one module is expelled during the second stage of parturition. This expelled module transmits a signal when it is outside the body (Palombi, et al, 2013). When this sensor system was applied on dairy farms studies reported a significant decrease on calf mortality, uterine infections and number of days open (Palombi, et al, 2013, Paolucci, et al, 2010.…”
Section: Introductionmentioning
confidence: 99%
“…Economic evaluations of sensor systems are therefore important. The adoption of sensors for calving detection on commercial dairy farms is still low (Palombi, et al, 2013). However, a system that helps farmers by predicting the moment of calving could be beneficial.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations